Analisis Karakteristik Akustik Dan Dinamik Micro-Perforated Panel Dengan Struktur Honeycomb Mengunakan FEM - Debby Perkasa; Afdhilla Afdhilla; Meifal Rusli (Politeknik Negeri Padang, 2022)
This study focuses on the discussion of the correlation of acoustic and dynamic characteristics of hybrid panels, namely Micro-perforated Panel (MPP) and Honeycomb (HC) structures. Acoustic characteristics in experimental studies are obtained by the sound absorption coefficient and Sound Transmission Loss. Meanwhile, the dynamic characteristics are obtained by the mode and frequency response analysis of numerical simulation methods. The results of these two characteristics serve as a benchmark for the development of experimental data studies/analysis. The purpose of this study is to obtain dynamic characteristics using mode and frequency response analysis through the finite element method. The development of this experimental study/analysis data is to overcome the drawbacks of experimental testing. The weakness obtained from experimental studies is that the stages are complicated and require a very large amount of money. The method in this study was carried out by numerical simulation using the finite element method using the Ansys 2019 R3 program. The results of this study obtained dynamic characteristics from the development of experimental study analysis methods using numerical simulations through the finite element method. Numerical simulation on the hybrid panel provides efficiency at the experimental testing stage. The results of the mode and frequency response analysis obtained by numerical simulation methods have similarities in the frequency range of high and low frequency values of sound absorption coefficient and soundtransmission loss.